2008
DOI: 10.1007/s10597-008-9131-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Self-assessment of Cultural and Spiritual Competency: Working with Asians and Asian Americans

Abstract: This study examines clinicians' own assessment of their cultural and spiritual competency in working with Asians and Asian Americans. Thirty clinicians, who are Asian Ethnic Minority Mental Health Specialists in the Northwest region of the United States, were surveyed to assess their perceived levels of cultural and spiritual competency. The study found that clinicians perceived themselves as being less spiritually competent than culturally competent and that most clinicians acknowledged the need for more trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…This study was designed in response to the results of a survey study conducted with Asian Ethnic Minority Mental Health Specialists in the Northwest region of the United States (Nagai, 2008). The study findings revealed that scores of ''spiritual competence'' on selfassessment were not as high as scores on ''cultural competence.''…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was designed in response to the results of a survey study conducted with Asian Ethnic Minority Mental Health Specialists in the Northwest region of the United States (Nagai, 2008). The study findings revealed that scores of ''spiritual competence'' on selfassessment were not as high as scores on ''cultural competence.''…”
Section: Methodsmentioning
confidence: 99%
“…Although spirituality is one of the most important aspects of diversity (Crook Lyon & Wimmer, 2005;Worthington, Kurusu, McCullough, & Sandage, 1996), it has been often neglected even in multicultural training (Nagai, 2008). As a result, a gap between what clinicians learn from their training and what they encounter when working with clients from various spiritual backgrounds has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Nagai (2008) found that practitioners perceived themselves to be lacking in sufficient levels of spiritual competency in working with Asian Americans. This finding is consistent with research documenting that most social work practitioners report receiving little information on spirituality during their graduate education (Canda & Furman, 2010).…”
Section: Implications For Practice •mentioning
confidence: 99%
“…Based on research that addresses the essential use of clients' cultural and spiritual background to help them unlock their potential problem-solving power (e.g., Nagai, 2008), we have used Gestalt techniques to help Asian clients who are nonexpressive. We used empty-chair techniques with more than 100 Asian clients and found that this technique deals with unspoken grief and bereavement issues, helps clients identify an alternative method to resolve relationship difficulties, and assists clients to express feelings surrounding a lack of childhood care or parental abandonment.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…It is also based on four characteristics observed from Asian clients that are research based: (1) connecting the meaning of shame in therapeutic interventions (Chan & Mendoza-Denton, 2008), (2) avoiding the loss of "face" in confronting relatives and friends (Cheung, Leung, & Tsui, 2009), (3) using alternative and complementary means to replace traditional therapy and direct confrontation (Choi & Kim, 2010;Lee, Goldstein, Brown, & Ballard-Barbash, 2010), and (4) using inner control and spirituality in resolving interpersonal guilt and conflict (Albertsen, O'Connor, & Berry, 2006;Nagai, 2008). It is worth noting that rapport building and establishment of trust between the therapist and the client must take place before the application of the Gestalt chair techniques with most Asian clients.…”
Section: Clinical Applicationsmentioning
confidence: 99%